2011
DOI: 10.1007/s10209-011-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

Linking the lonely: an exploration of a communication technology designed to support social interaction among older adults

Abstract: This article explores mixed methods data gathered from a pilot of a communication system prototype in the homes of 19 older adults over a period of 10 weeks. The system has been designed to enhance communication among both friends and strangers and has been developed as a possible tool to increase interaction in older adults suffering from social isolation and loneliness. The paper uses remote logging data to inform discussion of how such a technology was received and utilised over time in a home setting. Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 19 publications
(19 reference statements)
2
86
1
Order By: Relevance
“…Burmeister [14] highlights the importance of online communities to older adults for finding and sharing information, for emotional support about shared experiences, and for a sense of belonging. Studies have explored supportive technology to combat social isolation and loneliness [19,49,3], which may be related to physically relocating [34,48,54], or managing pain and chronic illness [8], or to understand perceived barriers to Internet use and online publishing, for example because of older adults' concerns about threats to personal privacy and security [1,32,43,67]. Studies of older adults' Internet use show a relative lack of 'online participatory culture' through social media compared to younger generations [10,27], raising issues and design implications for social inclusion and accessibility.…”
Section: Studies Of Technology Use In Retirementmentioning
confidence: 99%
“…Burmeister [14] highlights the importance of online communities to older adults for finding and sharing information, for emotional support about shared experiences, and for a sense of belonging. Studies have explored supportive technology to combat social isolation and loneliness [19,49,3], which may be related to physically relocating [34,48,54], or managing pain and chronic illness [8], or to understand perceived barriers to Internet use and online publishing, for example because of older adults' concerns about threats to personal privacy and security [1,32,43,67]. Studies of older adults' Internet use show a relative lack of 'online participatory culture' through social media compared to younger generations [10,27], raising issues and design implications for social inclusion and accessibility.…”
Section: Studies Of Technology Use In Retirementmentioning
confidence: 99%
“…For instance, Cao et al [4] identified design implications for facilitating family communication when its members are located in different time zones. Baecker et al [2], Cornejo et al [7], Garattini et al [10], Judge et al [15], Lindley [18], Muñoz et al [20], and Rodríguez et al [25] have adopted a different approach to dial wit that challenge. They designed specific domestic media spaces where remote family members, particularly older adults, can connect with each other using video-mediated communication and others kinds of messaging mechanisms.…”
Section: Related Workmentioning
confidence: 99%
“…More specifically, when working as a bridge for the adoption of Internet-based services like social applications and services capable of tackling social isolation. Examples of these were: Lindley et al PersonCard concept [19] which allowed for lightweight information to be sent and displayed within an older adult's home using a photo frame enhanced with touch-screen functionalities (much like a Tablet device); Lindley et al situated messaging device called Wayve [20] which was based on the same principles and made use of a device even similar to a Tablet; the Building Bridges project [11], a 12-inch touch screen device in a custom-made stand (the same principles as a Tablet) and a built-in phone handset, which was built with the goal of providing opportunistic social interaction among old adults who did not know each other before and which resulted in a very simplified use and in new social interactions (even outside the system); the Emnesh [29] which took advantage of the Internet connectivity and iPad features like an in-built camera and a virtual keyboard, for both capturing, exchanging and controlling photographs and messages around the screen and enabled older users to build rapport and find common interests; and Cornejo et al ambient SNS called Tlatoque [7] based on a multi-touch screen resembling a tablet, which communicated to Facebook to expose photographs in the user's home enabling a more natural interaction with the social information and contributing to enriching in-person encounters.…”
Section: Tablet Devices and Older Adultsmentioning
confidence: 99%